School Life Quality from the Perspective of Secondary School Students in Arab Schools in Palestine 1948 - Abu Khdair, Ghadeer Mostafa; Jabarien, Areen Khaled; Igbaria, Noran Sohail (Journal of Educational and Psychological Sciences, 2025)
The study aimed to assess the school quality of life among high school students in Arab schools in Palestine 1948. The descriptive analytical approach was used, with a sample of 200 students. The researchers developed a school quality of life scale covering four domains: health, social, academic, and emotional quality of life. The scale's validity and reliability were confirmed, with a Cronbach's alpha of 0.956, indicating high reliability.The results showed that the mean scores for the four domains were as follows: emotional quality of life (4.01), social quality of life (3.89), academic quality of life (3.85), and health quality of life (3.73), indicating a high level of school quality of life. There were no significant differences based on gender or mother's education, while differences appeared in favor of father's education "higher education," birth order favoring "first" and "last," and higher monthly income, reflecting the impact of social and economic factors on school quality of life.The study recommends adopting the scale as a standardized tool for assessing school quality of life and using the findings to guide educational policies towards improving the school environment to enhance student well-being. They also called for the development of educational programs focusing on health and emotional aspects and encouraged further research to expand the use of the scale in diverse educational settings, contributing to improving the quality of education and providing a positive school experience for students in Arab communities.
Keywords: Quality of School Life; Secondary School Students